Rations containing corn, sorghum grain, or wheat compared for weaned pigs - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The feed, required per pound of gain was similar for pigs fed corn, sorghum grain, corn-wheat, or sorghum grain-wheat diets. Pigs on the corn ration grew significantly (P<.05) faster. The sorghum grain, sorghum grain-wheat, and corn-wheat rations each produced similar gains.
Swine Industry Day 1971 is known as Swine Day, 1971
Keywords: Swine; Corn; Sorghum grain; Wheat